2020
DOI: 10.1002/aur.2347
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responses to a Putative Set‐shifting Task in Children with Autism Spectrum Disorder

Abstract: While much progress has been made toward understanding the neurobiology of social and communication deficits associated with autism spectrum disorder (ASD), less is known regarding the neurobiological basis of restricted and repetitive behaviors (RRBs) central to the ASD diagnosis. Symptom severity for RRBs in ASD is associated with cognitive inflexibility. Thus, understanding the neural mechanisms underlying cognitive inflexibility in ASD is critical for tailoring therapies to treat this understudied yet perv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Our findings support that these factors may substantially contribute to cognitive flexibility beyond ASD diagnosis per se. Moreover, different cognitive flexibility tasks should be considered in future research to offer a more comprehensive picture, given that the performance can be greatly influenced by the level of task difficulty and the nature of the task (i.e., different demands on the different domains of executive functions) (Dirks et al, 2020; Geurts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support that these factors may substantially contribute to cognitive flexibility beyond ASD diagnosis per se. Moreover, different cognitive flexibility tasks should be considered in future research to offer a more comprehensive picture, given that the performance can be greatly influenced by the level of task difficulty and the nature of the task (i.e., different demands on the different domains of executive functions) (Dirks et al, 2020; Geurts et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, task difficulty is an factor in explaining the mixed findings (Geurts et al, 2009). For example, examiners may set a longer stimulus presentation time and interstimulus interval to ensure the high level of behavioral performance (Dirks et al, 2020). Another explanation is that in tests tapping executive functions explicitly providing a high degree of task instructions (like the task-switching paradigm), the examiner provides the necessary structure and organization to act as external executive control for the subject and reducing the requirement for executive functions (including cognitive flexibility) (Eylen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Casey et al (2004) observed more prefrontal and parietal regions activated in adults compared with children (7-11 years), suggesting greater recruitment of these cortical regions across development. In Dirks et al (2020), the same task from Casey et al ( 2004) was used. The authors found typically developing children (7-12 years) had brain activation in the L posterior supramarginal gyrus/angular gyrus during shift trials.…”
Section: Neural Markers Of Cognitive Flexibility Across Development N...mentioning
confidence: 99%